1989
DOI: 10.1159/000125202
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle Delay and Inhibition of Gonadotropin and Prolactin Release during Sympathetic Nerve Degeneration after Superior Cervical Ganglionectomy of Rats

Abstract: The changes in the activity of the pituitary-gonadal axis during sympathetic nerve degeneration after superior cervical ganglionectomy (SCGx) were examined in female rats. In a first experiment SCGx performed at 24.00 h of diestrus II, 17 h in advance to the critical period for gonadotropin and prolactin (PRL) release, caused a delay of 1 day or more in estrous cyclicity, while SCGx at 24.00 h on estrus did not modify the estrous cycle. In a second experiment ovariectomized rats injected subcuta-neously with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…The possi bility that the increase in ACTH could be consequence of the stress response induced by disturbed homeostasis after SCGx should be considered. However, in a recent study the basal lev els of another stress hormone, prolactin, were not augmented in estradiol-progesterone-treated spayed rats 17 h after SCGx [7], while the ether-induced prolactin release increased after SCGx at an early phase of wallerian degeneration (i.e. 14 h after SCGx) but not at a later phase (i.e.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The possi bility that the increase in ACTH could be consequence of the stress response induced by disturbed homeostasis after SCGx should be considered. However, in a recent study the basal lev els of another stress hormone, prolactin, were not augmented in estradiol-progesterone-treated spayed rats 17 h after SCGx [7], while the ether-induced prolactin release increased after SCGx at an early phase of wallerian degeneration (i.e. 14 h after SCGx) but not at a later phase (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…Summarizing, the present results underline a role of periph eral sympathetic projections to the hypothalamic adenohypo physial axis in ACTH release mechanisms. PRL and ACTH are the only two adenohypophysial hormones so far examined that showed increased release during wallerian degeneration of sym pathetic nerves in the SCG territory, acute SCGx decreasing TSH, GH, LH, and FSH release in a number of paradigms [2,4,[6][7][8]. Although further experiments are needed to establish in a more detailed way the participation of SCG neurons in stress reaction, it is tempting to postulate that parallel central and pe ripheral noradrenergic channels convey information to the neu roendocrine system to allow the full response of the stress hor mones ACTH and PRL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…its preovulatory surge, to disrupt estrous cyclicity. The inhibitory effect of peripheral Wallerian degeneration on gonadotropin and PRL release was also found in Px rats (31), indicating that the effect observed was independent of the melatonin release taking place during Wallerian degeneration. In confirmation of the cycling in rats mentioned above.…”
mentioning
confidence: 72%
“…about 16-18 hours in advance of the critical period of gonadotropin and PRL release, caused 14 days delay of cycle, as shown by leukocytic diestrous vaginal smears, at the end of which the estrous cycle resumed. SCGx at 24:00 h on the day of estrus did not modify estrous cyclicity (31). The results indicated that sympathetic nerve degeneration after SCGx must coincide with the stimulus for gonadotropin release, e.g.…”
mentioning
confidence: 77%